Detection and characterization of a rhabdovirus causing mortality in black bullhead catfish, Ameiurus melas. Issue 7 (23rd March 2018) - Bedendo, Giulia; Panzarin, Valentina; Fortin, Andrea; Zamperin, Gianpiero; Pretto, Tobia; Buratin, Alessandra; Quartesan, Rosita; Sabbion, Matteo; Salogni, Cristian; Pascoli, Francesco; Toffan, Anna
Abstract: This study fully describes a severe disease outbreak occurred in 2016 in black bullhead catfish farmed in Italy. Affected fish showed nervous clinical signs as well as emaciations and haemorrhagic petechiae on the skin at the fin bases, abdomen and gills. Viral isolation in cell culture allowed the subsequent identification of a rhabdovirus, tentatively named ictalurid rhabdovirus (IcRV), through electron microscopy, immunofluorescence and whole genome sequencing (WGS). The newly isolated virus, together with 14 additional viral strains stored in our repository and detected during similar mortality episodes in the period 1993–2016, was phylogenetically analysed on the basis of the nucleoprotein and the glycoprotein nucleotide and amino acid sequences. The genetic distances among Italian IcRV strains were also estimated. Our results show that all the IcRV strains belong to the genus Sprivivirus and are closely related to the tench rhabdovirus (TenRV). Italian catfish production is constantly decreasing, mainly due to viral infections, which include the newly characterized IcRV. Data presented in this work will assist to investigate the molecular epidemiology and the diffusive dynamics of this virus and to develop adequate surveillance activities.